Implementasi Edukasi Kesehatan Herbal sebagai Upaya Promotif Pencegahan Gangguan Neurologi di Masyarakat - Anak Agung, Padmiswari; Nadya Treesna Wulansari; Kadek Buja Harditya (LOSARI DIGITAL, 2026)
This community service activity aimed to improve the knowledge and skills of the Tianyar Village community regarding the use of pegagan leaves (Centella asiatica) and mint leaves (Mentha arvensis) as antioxidant sources to support neurological health. The implementation methods included interactive counseling, demonstrations of herbal drink preparation, and evaluation through pre-test and post-test assessments. The number of participants in this community service was 50 participants. The analysis technique employed descriptive quantitative analysis to compare scores before and after the educational intervention, along with observation of participants’ practical skills. The results showed an average increase in knowledge scores of 28.2%, and 90% of participants were able to independently prepare the herbal drink. The activity also produced a simple, natural-based herbal infusion product that is easy to prepare. In conclusion, participatory-based education and training effectively enhanced community health literacy and practical skills as promotive and preventive efforts against mild neurological disorders.